Hubungan Konsentrasi Gas Amonia (NH3) dan Hidrogen Sulfida (H2S) dengan Gangguan Pernafasan (studi pada masyarakat sekitar TPA Pakusari Kabupaten Jember) - Zilfani Fuadiyah Haq; Isa Ma’rufi; Prehatin Trirahayu Ningrum (Pascasarjana Universitas Jember, 2021)
As much as 69% percent of waste in Indonesia ended up in the landfill and the problems continue to raise as it is managed by controlled landfill and open dumping systems. One of them was the emission of NH3 and H2S gases resulting from the decomposition of organic waste in the landfill which is irritant and dangerous if inhaled by the surrounding community at a certain level. This research was intended to analyze the correlation or relationship between the levels of NH3, H2S, and the respondent characteristics (gender, age, smoking habits, and history of disease) with the respiratory disorders sufferred by the community around Pakusari landfill. This research was an analytic observational study with quantitative approach. On its implementation, a cross sectional design was used. There were 642research population living 0-500 meters away from Pakusari landfill. The research samples consisted of the samples of respondentas many as 84 people and the air consisting of NH3, H2S, temperature, humidity, wind speed, and wind direction. The results showed that among 4 factor variables of individual characteristic, the age variable and the history of the disease variable had a significant relationship to the respiratory disorder variable (p-value = 0.060) and (p-value 0.036) and there was no relationship between the level variable of NH3 and H2S with variable respiratory disorders. Keyword: Ammonia, Hydrogen Sulphide, Respiratory Disorders, Communities